Provisioning an energy efficient with maximum coverage WSN through biological inspired sensor node placement - Abidin H.Z.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Bioinformatics; Energy efficiency; Energy utilization; Genetic algorithms; Optimization; Wireless sensor networks; biological inspired; coverage; Marking algorithm; Sensor node placement; Target monitoring; uniformity; WSN; Sensor nodes